Eco-sustainable production of bioactive sialyated-mucin (SiaMuc) glycopeptide from edible bird’s nest co-product - Tan, HuiYan; Lim, Hui-Zi; Seng, Joe Lim; Abdul Salam Babji,; Shahrul Razid Sarbini, (Penerbit Universiti Kebangsaan Malaysia)
Edible bird’s nest (EBN) is the dried salivary secretion of swiftlets during the breeding season. The widely consumed EBN for its highly unique nutrients has contributed to a high demand for international exportation. However, the processing of EBN to remove inedible materials (i.e. sand, dust, feathers) has contributed to several wastes. The disposal of this waste is hazardous to the environment and a waste of value due to abundant sialylated-mucin (SiaMuc) glycoprotein attached in the impurities. This “waste” is the processing co-product of EBN. Therefore, this study aimed to recover SiaMuc-glycoprotein in EBN co-product (EBNco-P) in the form of bioactive SiaMuc-glycopeptide. Through enzymatic hydrolysis, an eco-friendly alternative to transform insoluble SiaMuc-glycoprotein in EBNco-P into soluble bioactive SiaMuc-glycopeptide, valuable nutrients are separable from the impurities. Previously, through our research, this biotechnology has been applied to cleaned EBN. The research finds that the enzymatic hydrolysis of EBN that produces EBN glycopeptide has led to bioconversion into a high-grade product with enhanced nutritional bioavailability and functionality. Similar results are also revealed in the analyses of cleaned-EBN and EBN co-products. Whereby, the result revealed that the optimum hydrolysis period was at 90 min, in which the DH and enhanced solubility indicated a complete breakdown of glycoprotein into bioactive glycopeptide. This result is in line with the physicochemical analysis result. The hydrolysis has significantly decreased (p≤0.05) the EBN protein content, while the levels for peptide, glycopeptide, polysaccharides, and sialic acid showed the opposite. This study may contribute to broadening the EBN product development in terms of nutraceutical functionality. With the availability of low-cost EBN co-products, this study is beneficial not only scientifically, but also to the consumers, commercialization, and industrialization.